Impact of Material Property Variations and Sensor Positioning on the Coating Thickness Determination of Steel Sheets - Koll, Martin; Wöckinger, Daniel; Bramerdorfer, Gerd; Goldbeck, Gereon; Schuster, Stefan; Scheiblhofer, Stefan; Gstöttenbauer, Norbert; Reisinger, Johann (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper deals with investigations to determine the layer thickness of electrically conductive coatings on electrically conductive and ferromagnetic steel substrates. For this purpose, an eddy current sensor system with well-known analytical model for ideal conditions is used. Based on this, different coil setups are examined and compared with regard to sensor positioning. A robustness analysis against parameter fluctuations is carried out.